Revisiting the Metabolism of Donepezil in Rats Using Non-Targeted Metabolomics and Molecular Networking - Eun-Ji Park; Eui-Hyeon Kim; Ki-Young Kim; Ji-Hyeon Jeon; Im-Sook Song; So-Young Park; Kwang-Hyeon Liu (Pharmaceutics)
Background/Objectives: Although donepezil, a reversible acetylcholinesterase inhibitor, has been in use since 1996, its metabolic characteristics remain poorly characterized. Therefore, this study aims to investigate the in vivo metabolism of donepezil using liquid chromatography–high-resolution mass spectrometry (LC-HRMS) based on a molecular networking (MN) approach integrated with a non-targeted metabolomics approach. Methods: After the oral administration of donepezil (30 mg/kg) in rats, urine, feces, and liver samples were collected for LC-HRMS analysis. Chromatographic and spectrometric data were processed through MN and multivariate data analysis to identify the in vivo metabolites of donepezil. Results: A total of 50 metabolites were characterized, including 23 newly identified metabolites. Donepezil was biotransformed by O-demethylation, N-debenzylation, and hydroxylation, and these metabolites are further conjugated with glucuronic acid and sulfurous acid. N-Desbenzyldonepezil (M4), didesmethyldonepezil (M5), and N-desbenzyldonepezil (M4) were identified as the most abundant metabolites in urine, feces, and liver samples, respectively. Conclusions: The metabolic characteristics of donepezil in rats were comparable to those in humans, indicating that a rat is a reliable model for studying donepezil metabolism. This study indicates that a MN approach combined with a metabolomics approach is a reliable tool to identify unknown metabolites of drugs and drug candidates.